Commanding Eyes: Female Spectators and the Restoration Theatrical Repertoire - Jean I. Marsden (Etudes Epistémè)
This article explores the impact of women on the theatrical repertoire of the later seventeenth century in England. Female theatregoers at this time were largely anonymous, defined by their venue rather than by their names, however comments by playwrights indicate that pleasing this female audience, especially the elite women in the audience, could have a powerful effect on whether plays succeeded or failed upon the stage. The ladies were avid theatregoers, and their presence in the theatre auditorium was remarked upon, both positively and negatively, and their response to what they watched was studied and judged by those around them. For this reason, women frequently wore masks to the theatre in the early decades of the Restoration, in part to avoid being surprised by a bawdy play, such as William Wycherley’s The Country Wife. The article examines mask wearing within the theatre as it relates to female response to performance. Couched in terms of hypocritical mask wearing, Wycherley’s irate response to the ladies in his final play The Plain Dealer suggests that these elite women had the potential to negatively impact a play’s success. Paratexts from the end of the century indicate that playwrights perceived the ladies’ presence at theatre could assure a play’s success. In this way, the female audience was able to shape the theatrical repertoire.